Regulation of virulence in Chromobacterium violaceum and strategies to combat it - Venkatramanan, Mahendrarajan; Nalini, Easwaran (Frontiers in Microbiology, 2024)
Chromobacterium is a rod-shaped, Gram-negative, facultatively anaerobic bacteria with a cosmopolitan distribution. Just about 160 C. violaceum incidents have been reported globally, but then once infected, it has the ability to cause deadly septicemia, and infections in the lungs, liver, brain, spleen, and lymphatic systems that might lead to death. C. violaceum produces and utilizes violacein to kill bacteria that compete with it in an ecological niche.Violacein is a hydrophobic bisindole that is delivered through an efficient transport route termed Outer Membrane Vesicles (OMVs) through the aqueous environment. OMVs are small, spherical segments detached from the outer membrane of Gram-negative bacteria. C. violaceum OMV secretions are controlled by a mechanism called the quorum sensing system CviI/CviR, which enables cell-to-cell communication between them and regulation of various virulence factors such as biofilm formation, and violacein biosynthesis. Another virulence factor bacterial type 3 secretion system (T3SS) is divided into two types: Cpi-1 and Cpi-2.Cpi-1's needle and rod effector proteins are perhaps recognized by NAIP receptors in humans and mice, activating the NLRC4 inflammasome cascade, effectively clearing spleen infections via pyroptosis, and cytotoxicity mediated by IL-18-driven Natural Killer (NK) cells in the liver. In this paper, we attempt to interrelate quorum-controlled biofilm formation, violacein production, violacein delivery by OMVs and T3SS effector protein production and host mediated immunological effects against the Cpi1 of T3SS. We suggest a research path with natural bioactive molecule like palmitic acid that can act as an anti-quorum agent by reducing the expression of virulence factors as well as an immunomodulatory agent that can augment innate immune defense by hyperactivation of NLRC4 inflammasome hence dramatically purge C. violaceum infections.